Tuberculous meningits in adults in Turkey: Epidemiology, diagnosis, clinic and laboratory - Hosoglu, S; Geyik, MF; Balik, I; Aygen, B; Erol, S; Aygencel, SG; Satilmis, S (Springer, 2003)
A retrospective study was performed to assess the epidemiology, diagnosis, clinic, and laboratory of the patients with tuberculous meningitis (TBM) in a multicentral study. The medical records of adult cases with TBM treated at 12 university hospitals throughout Turkey, between 1985 and 1998 were reviewed using a standardized protocol. The diagnosis of TMB was established with the clinical and laboratory findings and/or microbiological confirmation in cerebrospinal fluid (CSF). The non-microbiologically confirmed cases were diagnosed with five diagnostic sub-criteria which CSF findings, radiological findings, extra-neural tuberculosis, epidemiological findings and response to antituberculous therapy. A total of 469 patients were included in this study. Majority of the patients were from Southeast Anatolia (164 patients, 35.0%) and (108 patients, 23.0%) from East Anatolia regions. There was a close contact with a tuberculous patient in 88 of 341 patients (25.8%) and with a tuberculous family member in 53 of 288 patients (18.4%). BCG scar was positive in 161 of 392 patients (41.1%). Tuberculin skin test was done in 233 patients and was found to be negative in 75. Totally 115 patients died (24.5%) of whom 23 died in 24 hour after admittance. The diagnosis was confirmed with clinical findings and CSF culture and/or Ziehl-Nelson staining in 88 patients (18.8%). Besides clinical criteria, there were three or more diagnostic sub-criteria in 252 cases (53.7%), two diagnostic sub-criteria in 99 cases (21.1%), and any diagnostic sub-criteria in 30 patients (6.4%). Since TBM is a very critical disease, early diagnosis and treatment may reduce fatal outcome and morbidity.
Keywords: close contact; diagnosis; epidemiological features; tuberculous meningitis